Occurrence of Cryptosporidium spp. in South African irrigation waters and survival of Cryptosporidium parvum during vegetable processing - Buys, E.M. (Elna Maria) (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2012.